Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, Aset Pajak Tangguhan dan Kepemilikan Manajerial terhadap Manajemen Laba - Muhammad Mirza Rifandy Akhbar; Andy Kartika (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study examines the effect of tax planning, deferred tax expense, deferred tax assets and managerial ownership on earnings management. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. The sample selection used the purposive sampling method and 138 samples were obtained. The results of the research show that the variables of tax planning, deferred tax expense, deferred tax assets and managerial ownership have an effect on earnings management. The data collection method is done quantitatively and the data processing technique uses multiple linear regression analysis. The data used is obtained from financial reports reported on the Indonesia Stock Exchange and can be downloaded through the idx.co.id website and analyzed using SPSS. The test results show that tax planning, deferred tax expense, deferred tax assets and managerial ownership have a positive effect on earnings management